2016
DOI: 10.1371/journal.pone.0163289
|View full text |Cite
|
Sign up to set email alerts
|

S-Propargyl-Cysteine, a Novel Hydrogen Sulfide Donor, Inhibits Inflammatory Hepcidin and Relieves Anemia of Inflammation by Inhibiting IL-6/STAT3 Pathway

Abstract: Anemia of inflammation (AI) is clinically prevalent and greatly threatens public health. Traditional remedies have raised controversy during clinical practice, calling for alternative therapies. We have recently found that hydrogen sulfide (H2S) inhibits inflammatory hepcidin, the critical mediator of AI. However, due to the chemical property of H2S, there remains an urgent need for a stable H2S donor in AI treatment. Here we reported that S-propargyl-cysteine (SPRC), a novel water-soluble H2S donor, suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The authors therefore concluded that ferritin, not inflammatory biomarkers, is responsible for controlling hepcidin levels in their group of IBD patients. These findings are potentially opening the possibility of using hepcidin suppressant (Eijk et al, 2014;M. Wang et al, 2016;Sebastiani, Wilkinson and Pantopoulos, 2016) drugs in order to correct IDA in patients with IBD.…”
Section: Iron Status In Inflammatory Bowel Disease (Ibd) Patientsmentioning
confidence: 95%
See 2 more Smart Citations
“…The authors therefore concluded that ferritin, not inflammatory biomarkers, is responsible for controlling hepcidin levels in their group of IBD patients. These findings are potentially opening the possibility of using hepcidin suppressant (Eijk et al, 2014;M. Wang et al, 2016;Sebastiani, Wilkinson and Pantopoulos, 2016) drugs in order to correct IDA in patients with IBD.…”
Section: Iron Status In Inflammatory Bowel Disease (Ibd) Patientsmentioning
confidence: 95%
“…For example in patients with ACD oral iron supplementation will be ineffective. Novel therapies, including hepcidin inhibitors (Eijk et al, 2014;M. Wang et al, 2016;Sebastiani et al, 2016) may prove to be particularly useful in cases of AI.…”
Section: Use Of Iron Supplements In Id and Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was documented that SPRC could prevent doxorubicin-induced cardiotoxicity ( Wu et al, 2016a ), which is similar to the effects of NaHS used in previous studies ( Wang et al, 2012 ). In addition, SPRC exhibited anti-inflammation ( Wang et al, 2016 ), anti-apoptosis and anti-oxidation in high glucose treated cardiomyocytes ( Yang et al, 2015 ).…”
Section: Donors Of Hydrogen Sulfidementioning
confidence: 99%
“…L -cysteine is a substrate for the endogenous production of H 2 S ( Salvi et al, 2016b ), mitochondria-targeted anethole dithiolethione (AP39), and (AP123) ( Gerő et al, 2016 ). Please see Table 1 for more information on common H 2 S donors as well as CBS and CSE inhibitors ( Lertratanangkoon et al, 1999 ; Lima et al, 2006 ; Szabó, 2007 ; Li et al, 2008 ; Kulkarni et al, 2009 ; Sun et al, 2009 ; Tyagi et al, 2009 ; Liu et al, 2010 , 2011 ; Wang et al, 2010 , 2016 ; Kodela et al, 2012 ; Predmore et al, 2012 ; Guo et al, 2013 ; Kondo et al, 2013 ; Lisjak et al, 2013 ; Luo et al, 2013 ; Martelli et al, 2013 , 2014 ; Barr et al, 2015 ; Fonseca et al, 2015 ; Iciek et al, 2015 , 2016 ; Liang D. et al, 2015 ; Polhemus et al, 2015 ; Tsai et al, 2015 ; Vannini et al, 2015 ; Chao et al, 2016 ; Qian et al, 2016 ; Salvi et al, 2016a ; Tain et al, 2016 ; Testai et al, 2016 ; Wu et al, 2016 ; Ali et al, 2018 ; Cao et al, 2018 ; Du et al, 2018 ; Ezeriņa et al, 2018 ; Liang et al, 2018 ; Lin S. et al, 2018 ; Ning et al, 2018 ; Powell et al, 2018 ; Qiu et al, 2018 ; Shimizu et al, 2018 ; Sone et al, 2018 ; Zhao et al, 2018 ; Zhou et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%